Analysis on Advantages and Disadvantages GAP 43 as Neuroregenaration Marker Examination in Rat Sciatic Nerve Injury - Ria Margiana (Journal of Global Pharma Technology, 2016)
Analysis focuses on the advantages as well as the disadvantages of using Growth Associated Protein 43 (GAP-43) as a neuroregeneration marker examination tool in a rat sciatic nerve injury examination. The sources of this research were attained from past scientific publications that had been published on the NCBI website. The research is unique because no past researches have ever been performed to ascertain the advantages and disadvantages of GAP-43 as a neuroregeneration marker examination tool in a rat sciatic nerve injury examination. The analysis will focus mostly on a research that was published on September 10, 2016. It focused on the GAP-43, a growth associated protein used in the treatment of a sciatic nerve injury in a Norway rat. The keywords used to attain the access the publication included GAP-43, neuroregeneration marker and sciatic nerve injury. The results of the search yielded a total of twenty-six full journal articles from PubMed Central and one scientific and medical abstract citation from PubMed. These are all publications that contain information pertaining GAP-43 and its applications. The materials for inclusion in the research were all journals summarizing the effects of GAP-43 on a sciatic rat. The participants of this review were program professor and myself. The materials for exclusion in the research included all publications with the exception of peer-reviewed scientific journals and publications from the PubMed or NCBI website. The conclusion of the study revealed that although GAP-43 has a few disadvantages, it is an effective neurogenerational marker in a rat sciatic nerve injury examination.Keywords: GAP 43, Neuroregenaration marker, Sciatic nerve injury